A global blueprint for enhancing opportunities for people with disabilities to access and succeed in higher education - Wimpenny, Katherine; Clouder, Lynn; Tombs, Gemma (Proceedings of the International Conference on Networked Learning, 2016)
This presentation will share the intercultural learning from the SWING project (Sustainable Ways to Increase Higher Education Students’ Equal Access to Learning Environments). This was a two-year project funded by EU Tempus, involving partnership between four European (EU), one Egyptian and two Moroccan higher education (HE) institutions. The overarching aim of the project was to bring together partner expertise to share best practice to support students with disabilities in accessing and optimizing their chance of succeeding in HE through the use of assistive technologies (AT). Research illustrates that there is still much work to be done in levelling higher education experiences for disabled students (Vickerman & Blundell, 2010). The project team investigated the current state of accessibility for disabled people in the EU and the partner countries in terms of national and international legislation, HE policy and practice. The International Classification of Functioning, Disability and Health (ICF) (WHO, 2001) was adopted which is the WHO's framework for health and disability that emphasises health and functioning, rather than disability. This conception of disability when applied in an HE context suggests the need to focus holistically on the education experience in its widest sense, thus enabling students to enjoy the full benefits of involvement in student life. An appreciative inquiry approach was adopted in line with a collaborative action research style ethos. The project aimed to capture the perspectives and alter attitudes and practice at all levels including students, academic and administrative staff, technical experts and senior managers. Having provoked change there is commitment in the partner countries to sustaining and building on what has been achieved. Partners are keen to disseminate the project outcomes nationally and internationally, and to become flagship institutions within their own countries. Mutual benefit for the EU universities has been felt through challenging taken-for-granted practice that might have lulled universities into thinking they had levelled the field for students with disabilities. For instance, the use of IT and AT had not been optimised in our own institution prior to this project, throwing local challenges into sharp relief.